Stray Dogs and Virtual Armies Radicalization and Recruitment to Jihadist Terrorism in the United States Since 9/11 - Jenkins, Brian Michael (RAND Corporation, 2011)
Since 9/11, "homegrown terrorists" have planned or implemented terrorist activities, supported others' terrorist activities, or become radicalized in the United States and traveled abroad to conduct activities against other countries or the United States. This paper examines the cases of homegrown terrorism, highlights lessons learned from those cases that suggest future actions, and includes a chronology of terrorist events in the United States.